A study on correlation between deficiency of vitamin D and knee osteoathritis among patients attending a tertiary care hospital in Andhra Pradesh - Rao, Komala; Ramesh, V. (International Journal of Research in Orthopaedics, 2020)
Background: The prevalence of vitamin D deficiency is the burning topic worldwide. Vitamin D deficiency is a under diagnosed medical condition since a significant proportion of the population in many countries and regions around the world have low serum 25-hydroxy (OH) vitamin D levels. The aim of this study was to investigate the association between serum vitamin D deficiency and knee osteoarthritis (OA). Methods: The study population consists of 200 patients divided into two groups, group 1 and group 2. Group 1 with 100 subjects with no clinical features of knee osteoarthritis served as controls and group 2 consists of 100 patients of patients diagnosed with knee osteoarthritis. Serum 25-OH vitamin D was measured in all the participants by the enzyme-linked fluorescence assay (ELFA) method and concentrations <20 ng/ml was considered as deficient. Results: In group 1, 47% were male and 53% were female whereas in group 2, 41% were male and 59% were female. In group 1, only 8% are vitamin D deficiency whereas in group 2, 61% have vitamin D deficiency. There was a significant association between serum vitamin D and staging of knee OA. Conclusions: The present study findings showed a significant association between serum 25-OH vitamin D deficiency and in patients with knee OA.